Strategic landscaping as an environmental solution and ecological connector: A study on the Paraibuna River, in Juiz de Fora/MG - Almeida, Karla Carvalho de; Souza, Rosiane de Oliveira; Netto, Maria Manoela Gimmler (Technical and Scientific Journal Green Cities, 2021)
.